Contribution of Medicine Ball Throw Training and Arm Muscle Power to Smash Ability in STKIP Harapan Bima Volleyball UKM - Muhadi, Muhadi; Saitya, Imaduddin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research used quantitative research where quantitative research is research in the form of numbers and analysis using statistics (Sugiyono, 2016). This research aims to determine the effect of arm muscle power on STKIP Harapan Bima volleyball UKM using medicine ball throw exercise. This type of research is experimental with a pretest-posttest design. And the population in this study was all Men’s and Women’s volleyball UKM STKIP Harapan Bima with a total 20 students divided into 2 groups, namely the High intensity interval training group and the control group. The sampling technique is quota sampling. The instrument used in this research is the medicine ball throw, namely the distance of the throw and the power ability of the arm muscles in the pushing movement. Data was collected using measurement techniques using the Bleep Test tool the measure VO2max. The data were analyzed using the MANOVA technique, using a 0.005. The research results showed that the effect of high intensity interval training on increasing VO2max was with a value of a p=0.005, then effect of running 30 meters with a value of p=0.005. From these two exercises, it turns out that high intensity interval training is better than running 30 meters in creasing VO2max. So based on the result, it can be concluded that there is a significant influence of medicine ball throw training and arm muscle power on smash ability in STKIP Harapan Bima Volleyball UKM.